Validity and Practicality: Study of E-Poster Development to Improve Environmental Literacy - Yovita, Yovita; Berlian, Mery; Sukor, Nur Suhaidah; Syafaren, Alaniyah; Yusra, Nelly (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The advancement of Era 4.0 technology has shifted the way humans think and work which were faster, more efficient, and effective in various sectors, including in education field. The Universitas Terbuka (UT) is one of university which has been existed for a long time and actively develop learning methods, for both online platforms and independent learning. In this context, it is important to support, develop and evaluate the distance learning system in utilizing all facilities including teaching materials, especially in terms of UT student practicum. This research aimed to increase environmental knowledge which intended to prepare people who understand and willing to overcome environmental problems by developing a QR-Code based E-Poster. This research implemented development research (Research and Development) with the ADDIE development model (Analysis, Design, Develop, Implementation, Evaluation). The results showed that the QR Code-based E-Poster developed had a high level of validity, practicality and effectiveness in increasing environmental literacy. Most of respondents gave positive responses to the use of E-Posters, such as easy to use, good layout, accessible, effective to deliver, clear text presentation, use of QR Codes, attractive color composition, good systematics, and efficiency in conveying information. In assessing the quality of media, the aspects of readability and understanding of concepts were very important, especially in the context of E-Posters. Conceptual reasoning as the respondent's ability to follow and understand the thoughts or concepts conveyed in the E-Poster was a significant factor. Good text comprehension includes ease of reading and understanding the information presented in the texts on E-Poster, Additionally, good language comprehension in this media included the respondent's ability to understand and interpret the information conveyed through the language used in the E-Poster. These findings highlighted the importance aspects in the development of E-Posters as effective learning and communication instruments. Keywords: e-poster, cyber-university pioneer , validity, practicality